2019
DOI: 10.1186/s41687-019-0105-6
|View full text |Cite
|
Sign up to set email alerts
|

PROMIS Fatigue short forms are reliable and valid in adults with rheumatoid arthritis

Abstract: Background Fatigue is prevalent and impactful in rheumatoid arthritis (RA). There is no standardized measure for its assessment nor data concerning the performance of PROMIS-Fatigue short forms (SFs) in people with RA. We evaluated the construct validity of 4-, 7-, and 8-item PROMIS-Fatigue SFs in RA patients across the range of disease activity. Methods Adult RA patients were recruited from an online patient community and an observational cohort from three academic med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 18 publications
5
43
0
Order By: Relevance
“…A systematic review described 23 different fatigue tools which were published before Patient-Reported Outcomes Measurement Information System (PROMIS) was developed. 17 18 In their review, they concluded that ordinal (Likert) and VAS, the Short Form 36 vitality subscale, the Functional Assessment of Chronic Illness Therapy Fatigue Scale (FACIT), the RA-specific Multidimensional Assessment of Fatigue scale (MAF) and the Profile of Mood States were validated and seemed sensitive to change. 17 19 20 Some scales are generic, and others are disease specific.…”
Section: Scope Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review described 23 different fatigue tools which were published before Patient-Reported Outcomes Measurement Information System (PROMIS) was developed. 17 18 In their review, they concluded that ordinal (Likert) and VAS, the Short Form 36 vitality subscale, the Functional Assessment of Chronic Illness Therapy Fatigue Scale (FACIT), the RA-specific Multidimensional Assessment of Fatigue scale (MAF) and the Profile of Mood States were validated and seemed sensitive to change. 17 19 20 Some scales are generic, and others are disease specific.…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…Pain can lead to poor sleep, depressed mood and fatigue, all of which are connected. 6 18 28 31 32 Also, more than 10% of patients with RA have fibromyalgia 33 and 10% report depression in ERA. 26 Behavioural and psychological factors are more likely explanations of fatigue in RA and not disease activity.…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…In patients with RA, PROMIS Fatigue SF scores were strongly correlated with the RAND 36 Vitality and Fatigue NRS ( r ≥ 0.85). A range of strong correlations was also observed between the different PROMIS Fatigue SF scores ( r ≥ 0.91) .…”
Section: Promis Fatigue Scalesmentioning
confidence: 76%
“…On the seven‐item PROMIS SF, 1% had scores at the lowest level (29.4) and highest (83.2) level. On the eight‐item PROMIS SF, 6% were at the lowest level (33.1) and 7% at the highest level (77.7), whereas on the four‐item PROMIS SF, 7% scores were at the lowest level (33.7) and 10% were at the highest level (75.8), well below the threshold of 15% for evidence of floor and ceiling effects . On the 29‐item PROMIS SF in patients with RA, 5.5% were at the lowest (33.7) level and 9% were at the highest levels (75.8); in patients with OA, 1.9% were at the lowest level and 14.9% were at the highest level; in patients with FM, 17.5% were at the lowest level and 2.1% were at the highest level; and in patients with SLE, 7.7% were at the lowest level and 9.7% were at the highest level .…”
Section: Promis Fatigue Scalesmentioning
confidence: 92%
See 1 more Smart Citation